Fine needle aspiration and core needle biopsy in the diagnosis of lymphadenopathy of unknown aetiology - Metzgeroth, Georgia; Schneider, Sven; Reiter, Sebastian; Hofmann, Wolf-Karsten; Marx, Alexander; Hastka, Jan (Annals of hematology, 2012)
The clarification of enlarged lymph nodes is a common issue in clinical routine. By now, open surgery with complete lymph node extirpation, followed by histopathology, is considered as standard. We investigated the value of fine needle aspiration (FNA) and core needle biopsy (CNB) when supporting the conventional morphology by immunotyping. In total, 101 lymph nodes (reactive, n = 19; lymphoma, n = 46; metastatic, n = 36) were examined. CNB specimens were sufficient for unequivocal diagnosis by histopathology in 95 %. The FNA cytology allowed a correct diagnosis in 49 %. When supported by immunocytology, the success rate improved to 72 %. By accepting “suspicious of” as correct diagnosis, the ratio increased to 91 %. Additional use of flow cytometry in 46 samples minimized the “suspicious of” diagnoses and increased the proportion of unequivocal diagnoses in FNA specimens to 87 %. Flow cytometry allowed a correct subtyping in 20 of 21 B cell lymphoma but recognised only one of five Hodgkin lymphoma. All eight reactive samples were correctly diagnosed by flow cytometry. In summary, CNB allows a reliable clarification of an unclear lymphadenopathy. FNA is a powerful first diagnostic approach, especially if cytology is supported by immunocytology. The most substantial contribution of flow cytometry in FNA is the discrimination between reactive lymphadenopathy and B cell lymphoma.
Gesehen am 28.11.2018